1968
DOI: 10.1111/j.1365-2133.1968.tb11952.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of Depigmented Skin in Kwashiorkor

Abstract: Observations were made on the epidermis of 10 Zulu infants with kwashiorkor and 5 control infants. The thickness of the kwashiorkor Malpighian layer was less than that of the controls; since no diflerences were apparent between kwashiorkor and control cell volumes, it was concluded that there are changes in the kinetics of cell migration in kwashiorkor.Measurements of junction granules in the basement membrane and spinous cell desmosomes indicate that they should be classified as separate entities.The lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Two articles describing histology reported atrophy of skin layers, but did not describe cutaneous immune cells [26][27]. Four articles described the “cutaneous inflammatory response”: They made small abrasions in the skin, and placed microscopy slides over the sites.…”
Section: Resultsmentioning
confidence: 99%
“…Two articles describing histology reported atrophy of skin layers, but did not describe cutaneous immune cells [26][27]. Four articles described the “cutaneous inflammatory response”: They made small abrasions in the skin, and placed microscopy slides over the sites.…”
Section: Resultsmentioning
confidence: 99%
“…Compromise of the skin barrier is the most clinically evident defect in children with oedematous malnutrition, classically described as the 'peeling paint' dermatosis of kwashiorkor [13]. Histologically, this is characterized by atrophy and effacement of the skin layers, hyperkeratosis and a pronounced cutaneous inflammatory response [14][15][16], providing a potential portal of entry for pathogens. An extensive enteropathy has long been recognized in children with severe malnutrition, characterized by mucosal inflammatory infiltrate, villous atrophy and compromised intestinal barrier function [17].…”
Section: (A) Mucosal Barrier Dysfunctionmentioning
confidence: 99%
“…Although some authors have noted, that at least two different variations exist, the skin lesions in oedematous malnutrition, DoK, look consistent across the studies, with a characteristic development over time . Histopathological studies have found atrophy of the stratum granulosum and stratum spinosum …”
Section: Discussionmentioning
confidence: 86%
“…Three papers, describing histological investigations on DoK, were identified. Their observations are not completely consistent, but all found epidermal atrophy in stratum granulosum and stratum spinosum . The findings are summarized in Table .…”
Section: Histologymentioning
confidence: 88%